In vitro Anthelmtic Activity of Nyctanthes arbortristis Leaves Against Ascaridia galli - Hazarika, Archana; Deka, Dilip Kumar; Sarma, Jadav; Phukan, Sulekha Choudhury; Hussain, Jakir (International Journal of Bio-resource and Stress Management, 2022)
The present study was undertaken during August 2018 to October 2019 to investigate the anthelmtic activity of crude extracts prepared from leaves of Nyctanthes arbortristis in water (AE), ethanol (EE) and hydro-ethanol (HEE) against Ascaridia galli. Adult Ascaridia galli of nearly equal size were divided into groups of six worms and placed in petri-dishes containing 25ml of phosphate buffer saline solution (PBS). They were exposed to the extracts at the rate of 10 mg ml-1 and 50 mg ml-1, respectively and observed for mortality at every 15 m, 30 m, 1 h, 2 h and 4 h of exposure. AE exhibited 100% mortality ofthe worms after 6 h of exposure irrespective of the concentrations used. In case of EE, 100% mortality was observed after 4 h of exposure at a concentration of 10 mg ml-1 while the exposure time was reduced to 2 h at a concentration of 50 mg -1ml with same efficacy. Similarly, at a concentration of 10 mg ml-1 and 50 mg ml-1, the exposure time was 4 h and 1h, respectively when exposed to HEE. The results suggest that in vitro anthelmintic activity of AEof N. arbortristis against Ascaridia galli was not concentration-dependent, but, time-dependent. On the other hand, anthelmintic activity of EE and HEE was both concentration dependent and time dependent. The hydro-ethanolic extract was found to be comparatively better among all the 3 extracts and was at par with piperazine hydrate when compared.